HEF1 promotes epithelial mesenchymal transition and bone invasion in prostate cancer under the regulation of microRNA‐14512. Issue 7 (9th May 2013) - Guo, Wei; Ren, Dong; Chen, Xiuting; Tu, Xiang'an; Huang, Shuai; Wang, Min; Song, Libing; Zou, Xuenong; Peng, Xinsheng
Abstract The principal problem arising from prostate cancer (PCa) is its propensity to metastasize to bones, and it's crucial to understand the mechanism of tumor progression to metastasis in order to develop therapies that may reduce the morbidity and mortality of PCa patients. Although we had identified that microRNA(miR)‐145 could repress bone metastasis of PCa via regulating epithelial–mesenchymal transition (EMT) in previous study, it is still unknown how miR‐145 regulated EMT. In the present study, we constructed a luciferase reporter system and identified HEF1 as a direct target of miR‐145. More importantly, HEF1 was shown to promote migration, invasion and EMT of PC‐3 cells, a human PCa cell line originated from a bone metastatic PCa specimen. And HEF1 was also shown to partially mediate miR‐145 suppression of EMT and invasion. Furthermore, inhibition of HEF1 repressed bone invasion of PC‐3 cells in vivo. Expression of HEF1 was negatively correlated with miR‐145 in primary PCa and bone metastatic specimens, but HEF1 was higher in samples which were more likely to commit to bone metastasis or those with higher free prostate‐specific antigen (fPSA) levels and Gleason scores. Taken together, these findings indicate that HEF1 promotes EMT and bone invasion in prostate cancer by directly targeted by miR‐145, and miR‐145 suppresses EMT and invasion, at least in part, through repressing HEF1. J. Cell. Biochem. 114: 1606–1615, 2013. © 2013 Wiley Periodicals, Inc.